2020
DOI: 10.1101/2020.07.07.190546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolutionary history of ACE2 usage within the coronavirus subgenusSarbecovirus

Abstract: AbstractSARS-CoV-1 and SARS-CoV-2 are not phylogenetically closely related; however, both use the ACE2 receptor in humans for cell entry. This is not a universal sarbecovirus trait; for example, many known sarbecoviruses related to SARS-CoV-1 have two deletions in the receptor binding domain of the spike protein that render them incapable of using human ACE2. Here, we report three novel sarbecoviruses from Rwanda and Uganda which are phylogenetically intermediate to SARS-CoV-1 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 82 publications
1
62
1
Order By: Relevance
“…However, the taxonomic distribution of this ORF is incongruent with whole-genome phylogenies in that ORF3d is intact in the pangolin-CoV more distantly related to SARS-CoV-2 (GX/P5L) but not the more closely related one (GD/1) ( Figure 4 ), a finding confirmed by the alignment of Boni et al, 2020 . New sequence data reveal similarly puzzling trends: ORF3d contains STOP codons in the closely related bat-CoV RmYN02 (GISAID: EPI_ISL_412977; data not shown), but it is intact in three more distantly related bat-CoVs discovered in Rwanda and Uganda, where it is further extended by 20 codons (total 78 codons) but shows no evidence of conservation with SARS-CoV-2 ( Wells et al, 2020 and pers. comm; data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…However, the taxonomic distribution of this ORF is incongruent with whole-genome phylogenies in that ORF3d is intact in the pangolin-CoV more distantly related to SARS-CoV-2 (GX/P5L) but not the more closely related one (GD/1) ( Figure 4 ), a finding confirmed by the alignment of Boni et al, 2020 . New sequence data reveal similarly puzzling trends: ORF3d contains STOP codons in the closely related bat-CoV RmYN02 (GISAID: EPI_ISL_412977; data not shown), but it is intact in three more distantly related bat-CoVs discovered in Rwanda and Uganda, where it is further extended by 20 codons (total 78 codons) but shows no evidence of conservation with SARS-CoV-2 ( Wells et al, 2020 and pers. comm; data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…New evidence points at the occurrence of recombination in SARS-CoV-2 ( Jackson et al, 2021 ; Latinne et al, 2020 ; VanInsberghe et al, 2021 ). This is not a novelty in coronaviruses ( Gribble et al, 2021 ) and previous analyses have shown that recombination has played an important role in the evolution of SARS-CoV-2 from its ancestors ( Andersen et al, 2020 ; Boni et al, 2020 ; Kirtipal et al, 2020 ; MacLean et al, 2021 ; Wells et al, 2021 ). Some recombinant sequences detected in the UK involve a breakpoint near the 5’ end of the spike gene from B.1.1.7 variants ( Jackson et al, 2021 ) but there has been no indication of changes in their phenotypic properties nor an increase in their frequency above the threshold for gaining the assignment of a new PANGO lineage.…”
Section: Sars-cov-2 Genetic Diversitymentioning
confidence: 93%
“…ACE2 is also the entry point for SARS-CoV and SARS-CoV-2 into cells. SARS-CoV-2 can efficiently use ACE2 as a receptor for cellular entry, with an estimated 10-to 20-fold higher affinity to ACE2 than SARS-CoV (Wrapp et al, 2020;Wu et al, 2020;Zhao et al, 2020), which underscores the ancestral ACE2-using viral lineage (Wells et al, 2020). Upon infection, ACE2 is occupied and endocytosed with virus particles, resulting in a reduction in the ACE2 expression on cells.…”
Section: Phys I Ology and Pathology Of H Uman Acein Sar S -Cov-infementioning
confidence: 99%